The Influence of Numeracy Skills on the Academic Achievement of Mathematics Education Students - Wawan Setiawan; Auditio Padaunan; Andi Sulfida (Journal of World Science, 2025)
This study aims to determine and analyse the effect of numeracy skills in solving mathematical problems on the learning achievement of students in the Mathematics Education Study Programme, Faculty of Mathematics and Natural Sciences, Makassar State University. Numeracy skills are essential competencies for prospective mathematics teachers to be able to apply mathematical concepts in various contexts. This study employs a quantitative approach using the ex post facto method. The research population consists of all active students from the 2021 and 2022 cohorts of the Mathematics Education Program at UNM, with a sample of 85 students selected using proportional random sampling. Numeracy ability data were collected through a validated structured essay test, while academic achievement data were obtained from students' Cumulative Grade Point Average (IPK) documentation. The data analysis technique used was simple linear regression analysis after undergoing normality and linearity tests. The results of the study indicate that: (1) The average numeracy ability of students was in the adequate category; (2) The average academic achievement (IPK) of students was in the very satisfactory category; (3) There was a positive and significant influence of numeracy ability on students' academic achievement with a coefficient of determination (R²) of 0.458. This indicates that 45.8% of the variation in students' academic achievement can be explained by their numeracy skills. The remainder is influenced by other factors. The implications of this study are the importance of strengthening numeracy skills in the curriculum to improve academic achievement and graduate competencies.